Harnessing digital disruption : how companies win with design thinking, Agile, and Lean Startup - Dennis, Pascal, 1957-; Simon, Laurent (New York : Productivity Press, 2020)
Our world has changed, probably for good. Until now, the shift from brick-and-mortar to the smartphone has been about service, cost, and convenience. Now, it's also a matter of public health. How do we win this uncertain new game? How do we prosper in a digital world? In a cool, readable style Harnessing Digital Disruption: How Companies Win with Design Thinking, Agile, and Lean Startup tells the story of a major multi-national organization facing digital disruption and looming irrelevance. In a compelling novel format, the book demonstrates how to harness the power of digital technology, methods and thinking on the path to revival and prosperity. It illustrates the situations, characters, and blockers you'll likely face as you progress through your journey. The setting is Singapore and the heady world of international banking, but the prescription, methods and lessons apply equally to manufacturers, utilities, hospitals, insurers, and government agencies. You will learn how to: Develop your Digital Transformation strategy and Innovation Portfolio Reform customer journeys, launch new digital offerings, and validate new beta businesses Develop senior leader digital literacy, and understanding of growth leadership De-risk your journey using a proven overall approach based on proven principles Cultivate a network of pragmatic entrepreneurs practicing a structured scalable innovation process This book offers clear and compelling guidance on what it takes to transform your organization for a digital world. Each chapter includes Study Questions to facilitate learning and discussion in workshop and classroom settings. .
OCLC-licensed vendor bibliographic record.
Keywords: Business enterprises -- Technological innovations; Organizational change; Success in business -- Technological innovations; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Production & Operations Management